O Projeto de identidade latino-americana de Manoel Bomfim na obra A América Latina: Males de Origem (1905) - NEVES, Cleiton Ricardo das (2010)
The present dissertation has an objective to build a Latin-Americanist debate unfolding the ideas of a Brazilian thinker named Manoel Bomfim (1868-1932), specifically with respect to Latin American identity. We intent to glimpse in which measurement the forethoughts of this Brazilian thinker makes of Latin America; if it can be considered a project of identification of the Latin American identity and as such design incorporates the mestizo man as bearer. This present project in Bomfim s work is especially based on the ideas of social parasitism, miscegenation. As an unfoldment of the dissertation, we focused on an analysis of Bomfim s intellectual biography connected with the intellectual discourse of the time. This locates spatially and temporally the Brazilian and foreign interlocutors of Bomfim. In this sense, we identify the streamlines that explicit or implicitly influenced the construction of a distorted conception of Latin America and of the Latin-American and which are refuted in Bomfim s works. Such refutations are the basis for Bomfim s discourse because his narratives are of resistance and his thought is characterized by the defense, as well as attacks the neo-colonization pretensions of both Europe and the United States, regarding Latin America. Finally, the fundamental conceptions that bring Bomfim originality to this discussion were worked; it s specificity and importance, both for the Latin-American identity as for a possible national identity. Herein, in a macro micro relation, Bomfim thinks Latin America from a view point in Brazil. He accentuates the miscegenation, the cultural plasticity and education as the fundaments of his Latin-American identification project.